Comprehensive Analysis of Endogenous Volatile Compounds, Transcriptome, and Enzyme Activity Reveals PmCAD1 Involved in Cinnamyl Alcohol Synthesis in Prunus mume - Zhang, Tengxun; Bao, Fei; Ding, Aiqin; Yang, Yongjuan; Cheng, Tangren; Wang, Jia; Zhang, Qixiang (Frontiers in Plant Science, 2022)
Floral scent is an important economic and ornamental trait of Prunus mume. The floral volatiles from most cultivars of P. mume in composition exist significant differences. Cinnamyl alcohol was one of the main floral volatile compounds with distinct abundances in different cultivars ‘Zaohua Lve’, ‘Zao Yudie’, ‘Fenpi Gongfen’, ‘Jiangsha Gongfen’ and ‘Fenhong Zhusha’. Based on the determination of endogenous volatiles of full-blooming flowers, vital enzyme activity and transcriptomes were comprehensively analyzed to screen the key potential genes involved in cinnamyl alcohol synthesis. Transcriptome combining with enzyme activity level analysis suggested that the expression levels of three PmCADs were highly correlated with the CAD enzyme activities in six cultivars. Further, phylogenetic tree and transcriptome analysis suggested that PmCAD1 and PmCAD2 might contribute to the cinnamyl alcohol synthesis. Relative expression analyses and enzyme activity assays showed that PmCAD1 played an important role in cinnamyl alcohol biosynthesis in vitro. Overall, this research lays a theoretical foundation for clarifying comprehensively the molecular biosynthesis mechanism of floral volatiles in P. mume.